The Influence of Overconfidence Bias, Herding Effect, and Loss Aversion on Investment Decisions in The Capital Market with Financial Literacy as A Moderating Variable - Firmansyah, Firmansyah (Profesional Muda Cendekia Publishing, 2023)
This study aims to examine the effect of overconfidence bias, herding effect, and loss aversion on investment decisions in the capital market with financial literacy as a moderating variable study on Generation Z novice investors in Malang. Sample determination is used by the accidental sampling method. The research data sources came from observations, interviews and questionnaires. Data analysis using the SEM-PLS approach with WarpPLS 7.0 software. The results showed that overconfidence bias, herding effect, and loss aversion had a positive and significant effect on investment decisions. Financial literacy can moderate the effect of overconfidence bias, and loss aversion on investment decisions. Financial literacy cannot moderate the influence of the herding effect on investment decisions.